Elevated anti-apoptotic shift in primary human aniridia limbal stromal cells following 48 hours supraphysiological glucose exposure, in vitro - Shanhe Liu; Shuailin Li; Shao-Lun Hsu; Fabian N. Fries; Zhen Li; Swarnali Kundu; Berthold Seitz; Maryam Amini; Shweta Suiwal; Tanja Stachon; Nóra Szentmáry (PLoS ONE, 2026)
Purpose Previous work demonstrated that supraphysiological glucose remodels TGF-β1 and NF-κB signaling in human limbal stromal cells (LSCs) and congenital aniridia-derived LSCs (AN-LSCs). The present study investigated whether the same metabolic stress also alters apoptotic pathways in these cells. Methods Primary LSCs (n = 12) and AN-LSCs (n = 8) were cultured for 48 hours in DMEM containing either normal (17.5 mM) or high (70 mM) glucose. Apoptosis was quantified by Annexin V/propidium iodide (PI) flow cytometry (FC). Expression levels of apoptosis-related genes—including CASP3/7/8/9/10, BCL2, BID, BAX, CDKN1A (p21), CDKN1B (p27), TNFα, XIAP, and BIRC5 (Survivin)—were assessed by qPCR. Protein levels of these markers were analyzed by FC, and TNFα protein concentrations in culture supernatants were measured by ELISA. Results High glucose significantly reduced the proportion of apoptotic cells in both LSCs (p = 0.0170) and AN-LSCs (p = 0.0181). In both cell types, CASP8 (p = 0.0448; p = 0.0171) and CASP10 (p = 0.0001; p = 0.0007) mRNA levels decreased, while XIAP (p = 0.0375; p = 0.0442) and BIRC5 (p = 0.0196; p = 0.0003) were upregulated. AN-LSCs additionally showed reductions in CASP3 (p = 0.0138) and CDKN1A (p = 0.0331), and exhibited lower BAX levels than LSCs under high glucose (p = 0.0255). Protein analysis corroborated these findings in AN-LSCs: Caspase-3 (p = 0.0154) and Caspase-8 (p = 0.0257) decreased, while Bcl-2 (p = 0.0284) and Survivin (p = 0.0467) levels increased. XIAP protein levels rose in both LSCs (p = 0.0451) and AN-LSCs (p = 0.0134). Conclusions A 48-hour exposure to 70 mM glucose induces a marked anti-apoptotic shift in human limbal stromal cells, more pronounced in cells derived from congenital aniridia patients. Together with previous evidence on TGF-β1 and NF-κB regulation, these findings suggest that limbal cells may mount an early protective response to metabolic stress, which could be harnessed therapeutically to manage aniridia-associated keratopathy through coordinated survival and stress pathways.